Marketing digital con IA - Ortega Arcos, Wagner Enrique; Ortega Roldán, Wagner Omar (Editorial Unión Científica, 2025)
The present chapter analyzes the role of artificial intelligence, AI, as a tool used in digital marketing, focusing its study on the Ecuadorian context. It begins with the recognition that AI has brought significant changes to communication processes, making its mastery essential for achieving efficient, personalized, and innovative campaigns. The research aimed to describe the integration of AI-based technologies such as chatbots, large language models, LLMs, programmatic advertising, emotion recognition, automated content generation, and predictive analytics. The methodology was qualitative-descriptive, based on a literature review and analysis of practical case studies developed by the author, including audiovisual products created with free AI tools. The findings indicate that these technologies optimize audience segmentation, enhance message personalization, reduce operational costs, and expand the reach of communication strategies. It was observed that, although countries like Ecuador show incipient development in the professional application of AI in digital marketing, there are significant opportunities for positioning in highly competitive markets through training and strategic use of these technologies.